2016
DOI: 10.1186/s13071-016-1625-z
|View full text |Cite
|
Sign up to set email alerts
|

Bat flies (Diptera: Nycteribiidae and Streblidae) infesting cave-dwelling bats in Gabon: diversity, dynamics and potential role in Polychromophilus melanipherus transmission

Abstract: BackgroundEvidence of haemosporidian infections in bats and bat flies has motivated a growing interest in characterizing their transmission cycles. In Gabon (Central Africa), many caves house massive colonies of bats that are known hosts of Polychromophilus Dionisi parasites, presumably transmitted by blood-sucking bat flies. However, the role of bat flies in bat malaria transmission remains under-documented.MethodsAn entomological survey was carried out in four caves in Gabon to investigate bat fly diversity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 47 publications
0
40
1
Order By: Relevance
“…This pattern is contrary to that which could be expected from bats that share caves or roosts over long periods. For example, it has been observed that bat species that share caves or roosts are prone to becoming infested by ectoparasites of other species (Obame-Nkoghe et al 2016). One possible explanation of the low ectoparasite overlap between bat species in cold and warm seasons is that the bats had low abundance and utilized separate roosts inside the cave.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is contrary to that which could be expected from bats that share caves or roosts over long periods. For example, it has been observed that bat species that share caves or roosts are prone to becoming infested by ectoparasites of other species (Obame-Nkoghe et al 2016). One possible explanation of the low ectoparasite overlap between bat species in cold and warm seasons is that the bats had low abundance and utilized separate roosts inside the cave.…”
Section: Discussionmentioning
confidence: 99%
“…Another facet of this research has shown that bat ectoparasites, specifically hematophagous bat flies of the families Streblidae and Nycteribiidae, are possible reservoirs and vectors for different zoonotic diseases, e.g. bacteria such as Bartonella and Rickettsia [3–5]; viruses such as rhabdovirus [6, 7]; and protozoans including the hematoparasite Polychromophilus [8, 9]. Hence, there is indirect evidence that bat ectoparasites may be responsible for the transmission of infectious diseases to their hosts, although it remains to be demonstrated that this could be via an oral route, specifically direct consumption of ectoparasites by bats.…”
Section: Introductionmentioning
confidence: 99%
“…Polychromophilus melanipherus has been recorded from presumptive eastern bent-winged bats in NSW and Queensland (Dew and McMillan, 1970; Mackerras, 1959). Bat flies, which are common, haematophagous external parasites of bats, are the accepted intermediate host (Dew and McMillan, 1970; Gardner and Molyneux, 1988; Mackerras, 1959; Obame-Nkoghe et al, 2016). The life cycle for P. murinus has been described (Gardner and Molyneux, 1988) and is assumed to be similar for P. melanipherus .…”
Section: Introductionmentioning
confidence: 99%